Color-encoded microcarriers based on nano-silicon dioxide film for multiplexed immunoassays - Li, Qiang; Zhang, Kaihuan; Wang, Tongzhou; Zhou, Xinying; Wang, Jia; Wang, Chen; Lin, Haixiao; Li, Xin; Lu, Ying; Huang, Guoliang (Analyst (London), 2012)
Multiplexed analysis allows researchers to obtain high-density information with minimal assay time, sample volume and cost. Currently, microcarrier or particle-based approaches for multiplexed analysis involve complicated or expensive encoding and decoding processes. In this paper, a novel optical encoding technique based on nano-silicon dioxide film is presented. Microcarriers composed of thermally grown silicon dioxide (SiO(2)) film and monocrystalline silicon (Si) substrate were fabricated. The nano-silicon dioxide film exhibited unique surface color by low-coherence interference. Hence the colors can be used for encoding at least 100 microcarriers loaded with films of different thickness. We demonstrated that color-encoded microcarriers loaded with antigens could be used for multiplexed immunoassays to detect goat anti-human IgG, goat anti-mouse IgG and goat anti-rabbit IgG, with fluorescent detection as the interrogating approach. This microcarrier-based method also exhibited improved analytical performance compared with a microarray technique. This approach will provide new opportunities for multiplexed target assay development.